Management of Stress at Workplace - Hirenkumar Pravinbhai Vacchani (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2020)
Stress is the body's reaction to any change that requires an adjustment or response. The body reacts to these changes with physical, mental, and emotional responses. Stress is a normal part of life. You can experience stress from your environment, your body, and your thoughts. Even positive life changes such as a promotion, family function or the birth of a child produce stress. This paper is designed to understand the indicators of stress and to find remedies for it. This study offers practical advice on how to handle work stress. We live in the life full of targets. There is difference between personal and professional targets but the targets at workplace create a next level stress which has become too common nowadays. This paper states that Work-related stress takes place when there is gap between actual work and the targets and sometimes because of unrealistic targets, too. The nature of stress at work, the causes and effects of stress, as well as remedies and preventions are discussed in the paper. What can be the role of the corporate culture in this process? What type of resources should be exploited for managing work stress? Let‟s discuss that in this paper.